CREDIBILITY AND POLITICAL COMMUNICATION OF MUHAMMAD SINEN, DEPUTY MAYOR OF TIDORE ISLAND FOR 2015-2020 PERIOD - BurhanudiN A. Muhamad; Nani Nurani Muksin (Perspektif Komunikasi: Jurnal Ilmu Komunikasi Politik dan Komunikasi Bisnis, 2019)
This study discussed the selection of mayor and deputy mayor of Tidore Islands for the 2015-2020 period, which was  attended  by  three  candidate  pairs  namel,  number  one  pair  of  Hamid  Muhammad-Abdurahim  Saraha (HARISMA), number two pair of Muhammad Hasan Bay-Mohtar Sangadji (MARASAI), and number three, pair of  Capt.  Ali  Ibrahim-Muhammad  Sinen  (SAFE).  The  theory  used  in  this  study  is  political  communication,  and political  credibility,  objectives  regarding  attitudes  and  regional  head  elections.  Using  a  qualitative  approach with the case study method, this study aims to describe the credibility of political figures related to expertise, and trust in the various abilities of the community during the 2015-2020 election of Tidore Islands deputy mayor. The results  of  the  study  indicated  that  the  credibility  of  political  figures  was  related  to  the  expertise  and  trust  of various  elements  of  society  during  the  2015-2020  election  of  Tidore  Island  deputy  mayor.  In  addition  to describing how the views on the construction of the attitude of political figures in a political event, this study also confirms the credibility of political figures with achievements or successes in political events. Keywords: Political Communication, Political Credibility, Political Figure